KEBIJAKAN EFISIENSI ANGGARAN PENDIDIKAN DALAM AKUNTABILITAS DI UIN SUNAN KALIJAGA YOGYAKARTA (Perspektif Manajemen Keuangan Pendidikan) - Eka Maftuhatil Riskiyah; Ach. Hanuji Akbar; Sabaruddin (re-JIEM (Research Journal of Islamic Education Management), 2025)
This study aims to analyze the educational budget efficiency policy at UIN Sunan Kalijaga Yogyakarta from the perspective of educational financial management, especially its empat on accountability and educational services. The research method used a qualitative approach with data collection through semi-structured in-depth interviews with relevant parties at the institution, non-participatory observation, and documentation studies. The results showed that the implementation of budget efficiency encourages more careful and transparent financial planning, thus improving institutional accountability. However, this policy also poses challenges in the form of a mismatch between budget allocations and the real needs of work units, which has an impact on the effectiveness of program implementation and human resource development. On the other hand, budget constraints trigger innovation in the utilization of digital learning technology, which supports more cost-effective and flexible education services. The benefits of this research are to provide conceptual contributions and evaluative material for higher education administrators in formulating budget efficiency policies that continue to ensure accountability and quality of education.